A Conjugative MDR pMG1-Like Plasmid Carrying the lsa(E) Gene of Enterococcus faecium With Potential Transmission to Staphylococcus aureus - Yan, Xiao-Mei; Wang, Jing; Tao, Xiao-Xia; Jia, Hong-Bing; Meng, Fan-Liang; Yang, Hui; You, Yuan-Hai; Zheng, Bo; Hu, Yuan; Bu, Xiao-Xia; Zhang, Jian-Zhong (Frontiers in Microbiology, 2021)
lsa(E) is a pleuromutilin, lincosamide, and streptogramin A (PLSA phenotype) resistance gene that was first described in S. aureus and was thought to have been transferred from Enterococcus sp. This study aimed to elucidate the prevalence of the lsa(E) gene among E. faecium isolates at a tertiary teaching hospital and to evaluate the transferability of the lsa(E) gene from E. faecium to S. aureus in vitro. A total of 96 E. faecium strains isolated from one hospital in Beijing in 2013 were analysed for quinupristin-dalfopristin (QDA) resistance genes and multilocus sequence typing (MLST). The transferability of QDA resistance between ten E. faecium strains and four S. aureus strains was determined by filter mating. Genome sequencing of the transconjugant was performed. A total of 46 E. faecium isolates (46/96, 47.92%) tested positive for lsa(E), while two isolates (2/96, 2.08%) tested positive for lsa(A). Thirty-six lsa(E)-positive strains (36/46, 78.3%) belonged to ST78. Among 40 mating tests, lsa(E) was successfully transferred through one conjugation at a frequency of 1.125 ×10-7 transconjugants per donor. The QDA resistance of the transconjugant N7435-R3645 was expressed at a higher level (MIC=16 mg/L) than the parent S. aureus strain (MIC=0.38 mg/L). NGS analysis of the transconjugant N7435-R3645 showed that the complete sequence of the lsa(E)-carrying plasmid, pN7435-R3645, had a size of 92,396 bp and a G+C content of 33% (accession no. MT022086). The genetic map of pN7435-R3645 had high nucleotide similarity and shared the main ORF features with two plasmids: E. faecium pMG1 (AB206333.1) and E. faecium LS170308 (CP025078.1). The rep gene of pN7435-R3645 showed 100% identity with that of pMG1, though it did not belong to the rep1-19 family but instead a unique rep family. Multiple antibiotic resistance genes, including lsa(E), aadE and lnu(B), erm(B), ant6-Ia, and lnu(B) were present on the plasmid. In conclusion, a new lsa(E)-carrying plasmid that can be transferred by conjugation from E. faecium to S. aureus in vitro was identified. This new plasmid may act as a vector in the dissemination of antimicrobial resistance among species.